Penggunaan Galon Air Mineral Bekas untuk Meningkatkan Sanitasi pada Pedagang Makanan Keliling di Wilayah Depok Timur - Afif Amir Amrullah; Ayu Anggraeni Dyah Purbasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Limited sanitation facilities among street vendors, particularly those selling meatballs, chicken noodles, and porridge, often pose a problem that impacts food safety. One common practice is repeatedly washing bowls and spoons with just a bucket of water, followed by drying the utensils with a cloth. This contaminated water can transmit pathogenic microorganisms that cause foodborne illnesses, increasing the risk of health problems for consumers. This problem requires a practical solution that street vendors can implement, taking into account limited space, mobility, and operational costs. This community service activity used a pre-experimental design method with a simple technological engineering approach to improve the sanitation of tableware. The innovation developed was a portable bowl washer made from used mineral water gallons, modified to be mobile, efficient, and water-efficient. The manufacturing process included design, assembly, testing, and evaluation with street vendors. Success was measured by observing the level of cleanliness of the tableware before and after use, as well as assessing the level of satisfaction and ease of use by the vendors. The results showed that the implementation of this portable sanitation device increased the effectiveness of tableware washing, reduced the repeated use of dirty water, and minimized the risk of cross-contamination. Partnering vendors stated that the device is practical, lightweight, and doesn't disrupt their sales activities. They hope this innovation will be replicated by other vendors and that local governments will consider implementing it as a standard for mobile food sanitation. This effort will not only improve the hygiene of eating utensils but also contribute to preventing foodborne illnesses in the community.